The Integration of Digital Storytelling in Arabic Language Learning: A Pedagogical Approach to Speaking Skill Development - Safii, Randi; Tjalau, Cutri A.; Pakaya, Nurul Aini (Assuthur: Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to examine the effectiveness of Canva-based digital storytelling as a pedagogical tool for enhancing Arabic speaking skills among students of the Arabic Language Education program. Employing a mixed-methods approach, the research involved 25 students who participated in a five-session instructional intervention. Data were collected through pre- and post-tests (quantitative) as well as classroom observations, semi-structured interviews, and written reflections (qualitative). Results revealed a statistically significant improvement in speaking proficiency particularly in fluency, pronunciation, vocabulary use, and sentence structure as confirmed by paired-sample t-test analysis (p < 0.05). Qualitatively, students reported increased intrinsic motivation, reduced speaking anxiety, and greater self-confidence, attributed to the integration of oral narration with self-designed visual elements. The approach aligns coherently with key second language acquisition theories, including Task-Based Language Teaching (TBLT), Krashen’s Input and Affective Filter Hypotheses, and Swain’s Output Hypothesis. Furthermore, the use of Canva exemplifies effective integration of Technological Pedagogical Content Knowledge (TPACK), merging technological, pedagogical, and Arabic linguistic content knowledge. These findings affirm that digital storytelling is an innovative, contextual, and effective alternative instructional strategy for developing Arabic speaking skills in higher education, effectively addressing the limitations of conventional teaching methods, which are often monotonous and fail to foster active student engagement.